POLITICAL PARTIES AND ELECTIONS: PROCESS OF ELECTIONS AND ACTION STRATEGIES (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
this article examines the structural and functional role of political parties within democratic systems, focusing particularly on the electoral process and party action strategies. The study analyzes how political parties mobilize voters, formulate policy platforms, and develop strategic approaches during election campaigns. Additionally, the article highlights the significance of transparent electoral mechanisms, legal frameworks, and social engagement in ensuring fair elections. The research draws on theoretical perspectives from political science and comparative politics to provide a comprehensive understanding of contemporary electoral practices and party behavior.